Intrahousehold specialization in housework in the United States and Denmark - Jens Bonke; Mette Deding; Mette Lausten; Leslie Sundt Stratton (Institute for the Study of Labor (IZA), 2007)
Objective: Focusing on housework activities, we construct a gender neutral composite index measure of intrahousehold specialization. We hypothesize that the degree of specialization is influenced by economic notions of efficiency, as well as by time constraints and egalitarian values. Methods: Employing time use data on US and Danish couples, we model specialization using a multivariate two-limit Tobit. Results: We analyze the comparability of reported time use and our specialization index using different types of data. We find evidence that Danish households specialize less than American households and postulate that this cross-national difference is a result of the more egalitarian family culture within Scandinavia. A finding that children are associated with significantly increased specialization in the US but not in Denmark is attributed to the subsidized childcare services provided by the Danish welfare system. Conclusion: Intrahousehold specialization in housework varies with economic circumstances, time constraints, and social values.
urn:nbn:de:101:1-20080401533
Keywords: 330; Hausarbeit; Familienökonomik; Geschlecht; USA; Dänemark